GROS INGRATITUDE AS A REASON OF REVOKING GIFTS - Alen Lalić; Ivan Rančić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Contracts that do not contain any shortcomings, and are fully fulfilled, in practice can rarely be terminated, all because of the civil principle that the contract is a statutory relationship between the parties. The gift contract is an exception, because it can be terminated through the institute of revocation of the gift, although it does not contain any defect, and is fully fulfilled. The gratuitousness of the gift contract is the reason why the legislator enables the termination of the fulfilled and valid gift contract. The Law on Obligations recognizes two reasons for revocation based either on the fact that the material circumstances on the part of the donor subsequently changed so much that the material existence of the donor is endangered, or on the fact that the other party is guilty of terminating the contract. The guilt of the other party or the donee does not refer to the guilt regarding the content of the gift contract and its fulfi llment, because the contract is duly fulfilled. It is moral that the donee is grateful for the gift made, and that he does not take actions towards the donor that would lead to a significant disruption of mutual relations. However, the same donee forgets his “moral obligation”, and after the gift is made, he begins to behave in a rude and immoral way towards the donor. That is why it is possible for the donor to revoke the donation contract through the institute due to gross ingratitude, which requires the fairness, even though the contract is fulfilled, because it is immoral for such a donee to keep what he received for free from the donor. The aim of this paper is to develop the concept of revocation of gifts due to gross ingratitude under the provisions of the current Law on Obligations. The present paper will also elaborate the notion of gross ingratitude according to the legal rules of OGZ, all considering that the same rules are (still) applicable to those gift contractual relations that arose before the entry into force of the current Law on Obligations.